2017
DOI: 10.1002/cptc.201700176
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐State Pathways of Four‐Coordinate N,C‐Chelate Organoboron Dyes

Abstract: The excited‐state behavior of four‐coordinate N,C‐chelate organoboron dyes, based on arylisoquinoline ligands with varying degree of charge‐transfer character, was characterized. Data related to excited triplet state formation, oxygen quenching, and singlet‐oxygen formation were obtained. The results jointly rationalize the previously observed high photostability of the dyes in air‐equilibrated media. Furthermore, femtosecond transient absorption experiments enabled the spectroscopic visualization of the excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…[3,[9][10][11][19][20][21][22][23][24][25][26][27] As parto fo ur own research program we have developed borylated arylisoquinoline (BAI) dyes,w hich in their N,C-chelate variant are strongly emitting, solvatochromic, and two-photon-absorbing charge-transfer fluorophores with applicationp otentiali nb ioimaging. [9,10,28] With the idea to further enricht he photophysicso ft his fascinating platform we have built on their biaryl structure,w hich providesameanst oa rrive at dyes with helical chirality and the correspondingo bservation of interesting chiropticalp roperties, including the detection of circularly polarized luminescence (CPL). [29][30][31][32] The phenomenoni sw ell established for supramolecular assemblies or nanostructures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,[9][10][11][19][20][21][22][23][24][25][26][27] As parto fo ur own research program we have developed borylated arylisoquinoline (BAI) dyes,w hich in their N,C-chelate variant are strongly emitting, solvatochromic, and two-photon-absorbing charge-transfer fluorophores with applicationp otentiali nb ioimaging. [9,10,28] With the idea to further enricht he photophysicso ft his fascinating platform we have built on their biaryl structure,w hich providesameanst oa rrive at dyes with helical chirality and the correspondingo bservation of interesting chiropticalp roperties, including the detection of circularly polarized luminescence (CPL). [29][30][31][32] The phenomenoni sw ell established for supramolecular assemblies or nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been dedicated to the development of synthetically flexible platforms which enable the photophysical fine‐tuning of the dyes . As part of our own research program we have developed borylated arylisoquinoline (BAI) dyes, which in their N,C‐chelate variant are strongly emitting, solvatochromic, and two‐photon‐absorbing charge‐transfer fluorophores with application potential in bioimaging . With the idea to further enrich the photophysics of this fascinating platform we have built on their biaryl structure, which provides a means to arrive at dyes with helical chirality and the corresponding observation of interesting chiroptical properties, including the detection of circularly polarized luminescence (CPL) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photophysical characterization of the dyes 16 – 19 was completed by nanosecond laser-flash photolysis experiments in acetonitrile [45]. The laser excitation (λ exc = 308 nm) of the dyes 16 and 17 in nitrogen-purged solution yielded transient absorption spectra with a broad band at λ max = 610 and 600 nm, respectively (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NˆC-chelate organoboron dyes, including those with arylisoquinoline ligands (19-20, Figure 11), display high stability in air-equilibrated media, and an excited state intramolecular charge-transfer (ICT) character leading to high Stokes shifts, solvatofluorochromic behavior, and high photochemical stability [60,61]. Pischel and coworkers [61] found that the π-extended system 20a-c (Figure 11) exhibits unique two-photon absorption (TPA) properties in the NIR region.…”
Section: -Arylisoquinolines-derived Nˆc-chelatesmentioning
confidence: 99%